Elevated BLyS levels in patients with systemic lupus erythematosus: Associated factors and responses to belimumab. (April 2016) - Roth, D A; Thompson, A; Tang, Y; Hammer, A E; Molta, C T; Gordon, D
Introduction: Patients with systemic lupus erythematosus (SLE) with B-lymphocyte stimulator (BLyS) levels ≥ 2 ng/mL are at increased risk of flare. A regression analysis was undertaken to identify routine clinical measures that correlate with BLyS ≥ 2 ng/mL. Efficacy and safety of belimumab 10 mg/kg were examined in patients with BLyS ≥ 2 ng/mL and < 2 ng/mL. Methods: Data from BLISS-52 and -76 ( N  = 1684) were pooled post hoc. A univariate logistic regression was employed to identify factors predictive of baseline BLyS ≥ 2 ng/mL. Factors significant at the 0.05 level then entered a stepwise logistic regression as covariates. Efficacy endpoints included SLE responder index (SRI), ≥ 4-point reduction in Safety of Estrogens in Lupus National Assessment–Systemic Lupus Erythematosus Disease Activity Index (SELENA-SLEDAI) and risk of severe flare over 52 weeks. Adverse events (AEs) were analyzed for each treatment arm and BLyS subgroup. Results: Baseline predictors of BLyS ≥ 2 ng/mL included positive anti-Smith (≥ 15 U/mL), low complement (C) 3 (< 900 mg/L), anti-double-stranded DNA (anti-dsDNA) 80–200 and ≥ 200 IU/mL, immunosuppressant usage, proteinuria, elevated C-reactive protein (CRP), and low total lymphocyte count for all patients. Belimumab 10 mg/kg led to significantly greater SRI responses over 52 weeks versus placebo in both BLyS subgroups, though treatment differences were numerically greater at Week 52 in the BLyS ≥ 2 ng/mL group (24.1%, p  < 0.0001) compared with BLyS < 2 ng/mL (8.2%, p  = 0.0158). Results were similar for ≥ 4-point reduction in SELENA-SLEDAI. Risk of severe flare over 52 weeks was significantly reduced with belimumab 10 mg/kg versus placebo in the BLyS ≥ 2 ng/mL group ( p  = 0.0002). AEs were similar across treatment arms and BLyS subgroups. Conclusions: Positive anti-Smith, low C3, anti-dsDNA ≥ 80 IU/mL, immunosuppressant usage, proteinuria, elevated CRP, and low total lymphocyte count were predictors of BLyS ≥ 2 ng/mL. Monitoring these factors could identify patients with BLyS ≥ 2 ng/mL who are at risk of flare.